Rola samorządu gminnego Bełchatowa w społeczności lokalnej - Błaszczyk, Andrzej (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
The paper discusses the role and activity of the local self-government in Poland basing on the case of Bełchatów community. In the first part of the work, the most important attributes of the contemporary local administration were presented. The author shows a new approach to managing local communities over Europe and their capacity to achieve their tasks effectively. In the second half of the work, there were described various activities of Municipal Council and Bełchatów local administration, including their cooperation with the inhabitants in the years 1995-1999 and afterwards. The most crucial investments of the local council were presented taking into account the conditions under which the decisions were made.